An Investigation of Phenol Adsorption from Aqueous Solution Using Solid Adsorbents - Insuwan, Wilaiporn; Saosai, Nantana (Naresuan University Journal: Science and Technology (NUJST), 2019)
This study reports on removal of phenol on various solid adsorbents namely, activated carbon (AC), zeolite LTL in 2 forms, K-LTL and H-LTL. This work was performed by batch adsorption techniques. The effect of adsorbent, pH and temperature were determined to find out the optimal condition. The amounts of adsorbed phenol were interpreted using Langmuir and Freundlich. K-LTL zeolite was found to be most effective for the removal of phenol than H-LTL and AC. The optimum conditions for maximum adsorption were K-LTL being used as an adsorbent, at pH 4. Moreover, it was found that the adsorption was enhanced with increasing temperature. This results showed that the K-LTL zeolite exhibit a better an adsorbent for the removal of phenol from aqueous solutions. Furthermore, thermodynamic parameters including Gibbs free energy (ΔG°), enthalpy (ΔH°) and entropy (ΔS°) were also determined. The results indicating the adsorption is spontaneous and endothermic process.   Keywords: Zeolite LTL, Activated carbon, Phenol, Adsorption isotherm